Psychometric properties of knowledge, attitude, and practice on pharmacogenovigilance in drug safety questionnaire in medicine and pharmacy students: based on Exploratory Factor Analysis - Yau, Adamu; Husain, Rohayah; Abd Aziz, Aniza; Zahri Johari, Mohd Khairi; Rahman, Ab Fatah; Elkalmi, Ramadan Mohamed Mahmod; Jamilu, Ya'u; Haque, Mainul (Journal of Applied Pharmaceutical Science (http://www.japsonline.com), 2015)

(untitled)
Integration of Pharmacogenomics and Pharmacovigilance in the curricula of future healthcare professionals isessential towards individualized medicine and drug safety. Researchers are lacking in Knowledge, attitude and practice regarding pharmacogenovigilance in drug safety among Malaysian future health professionals. Thisstudy is to develop and validate a reliable questionnaire for evaluation of knowledge, attitude and practice of future Doctors and Pharmacists concerning Pharmacogenovigilance in drug safety. A 49-item self-administeredquestionnaire was developed from the literature. The content was validated by a panel of relevant expertsfollowed by face validity. A pilot study on 100 respondents was conducted for reliability, followed by a crosssectional